The Evidence of Size Effect During Bull and Bear Markets - Mohd Yacob, Nathrah (2006)
Most studies documenting an inverse relation between firm size and risk adjusted returns on stocks assume constant risk over time with the well known Constant Risk Model/ Capital Asset Pricing Model.This thesis examines the relationship between abnormal returns and the portfolio sizes as to determine if there is an existence of size effect although the risks are allowed to vary in different market conditions as with a different model known as the Varying Risk Model on Malaysian stock market.For comparison purposes, the Constant Risk Model is also being tested on the same data.The results indicated that there was an insignificant evidence of size effect on the sample selected that includes all companies listed in the Kuala Lumpur Stock Exchange Composite Index during the period from 1994 to 2003 with the used of Constant Risk Model. When the sample period was split into bull and bear months and the sample data were examined according to the months, there were significant differences of abnormal returns and systematic risks between bear and bull markets using the Varying Risk Model.In addition,with the inclusion of all months in the sample period, the reversal of size effect is seen during bear months when the largest firms’ portfolio outperformed the smallest firms’ portfolio.However, when the crisis period is excluded from the sample period,the size effect made its appearance during both market conditions.It is concluded that earlier reported performance of small firm stocks have been overstated because of an implied assumption of constant risks in bull and bear market.Benefit in investing in small firm stocks is significant only during January bear months.With these findings,fund managers and investors could play important roles by switching from the well known Constant Risk Model to Varying Risk Model in determining the right investment strategies that generate appreciable abnormal returns for their portfolios.The findings are also significant to the policy maker or regulators to set guidelines and regulations for stock market participants whether they are retail or institutional investors in investing in Malaysian stock market during different market conditions